50 years of the first ethics commission in Germany: the Ulm Ethics Commission in an international perspective - Steger, Florian; Kosenko, Oxana (Frontiers in Public Health, 2023)
Background: The creation of the legal framework to recognize rights of patients and participants in clinical trials began in Germany in the 19th century. However, the ethical review of medical research in terms of the protection of rights and welfare of human subjects has only become a widespread practice since the establishment of ethics commissions. The first ethics commissions emerged at universities under the influence of the German Research Foundation. The widespread establishment of ethics commissions began in the Federal Republic of Germany in 1979, after the adoption of the recommendation of the German Medical Association for the establishment of ethics commissions. Materials and methods: We analyzed unpublished archival documentation of the Ethics Commission of the University of Ulm and evaluated it based on a thorough review of research works on the history of international and German ethics commissions. For sources examination, we implemented the historical-critical method. Results: The first ethics commission in Germany was set up at the University of Ulm in 1971/72. The reason for that was that the German Research Foundation required grant applications for medical research involving human subjects to be reviewed by an ethics commission. Initially the commission was created at the Center for Internal Medicine and Pediatrics, its authority grew over time until in 1995 it became the central Ethics Commission for the entire University of Ulm. Before the adoption of the Tokyo revision of the Declaration of Helsinki in 1975, the Ulm Ethics Commission developed its own guidelines for the conduct of scientific investigations on humans based on international ethical principles. Conclusion: The Ethics Commission of the University of Ulm must have been established between July 1971 and February 1972. The German Research Foundation played a decisive role in the establishment of the first ethics commissions in Germany. The Universities had to create ethics commissions in order to be able to obtain additional funds from the Foundation for their research. Thus, the Foundation initiated the institutionalization of the ethics commissions in the early 1970s. The functions and composition of the Ulm Ethics Commission were similar to other initial ethics commissions of the time.